Role and regulatory mechanism of GPR37 in neurological diseases - Liu, Shuo; Bai, Tao; Liu, Xun; Zhao, Wenwen; Li, Xin; Sui, Yi; Feng, Juan (Frontiers in Cellular Neuroscience, 2025)
G protein-coupled receptor 37 is an orphan Class A GPCR predominantly expressed in the central nervous system (CNS), implicated in diverse physiological and pathological processes. This review summarizes current advances in the structural and functional understanding of GPR37, including its genomic localization, receptor architecture, endogenous ligands, and downstream signaling pathways. Emphasis is placed on its cell-type-specific expression across neurons, astrocytes, microglia, and oligodendrocytes, and how this expression dynamically shifts under pathological contexts such as Parkinson’s disease, stroke, and demyelinating disorders. GPR37 modulates neuroinflammatory responses, apoptosis, and oxidative stress through context-dependent mechanisms shaped by its ligands, including prosaposin, neuroprotectin D1, and osteocalcin. Additionally, GPR37 dysfunction–especially via receptor misfolding and ER stress–contributes to neuronal vulnerability. We further discuss its emerging role as a pharmacological target and potential biomarker in CNS disorders. By integrating findings across molecular, cellular, and disease models, we propose a context-dependent framework positioning GPR37 as a multifunctional regulator and therapeutic candidate in neurodegeneration.